ANALISIS RESPON MAHASISWA TERHADAP MEDIA AUTOPLAY DENGAN METODE MEA SEBAGAI MEDIA PEMBELAJARAN MATAKULIAH GENETIKA DI IKIP BUDI UTOMO MALANG - Primadya Anantyarta; Ririn Listya Ika Sari (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2017)
One of the efforts in accommodating 21st century learning in IKIP Budi Utomo Malang, especially in Biology Education Program in Genetics Subject is with the development of Auto Play media with MEA (Means-Ends-Analysis) method. This study aims to produce products in the form of learning media based on Genetics Auto Play with MEA method. This development research uses Research and Development (R & D) method with 4D development model which has Define, Design, Develop, and Disseminate stages. In this research is done up to development stage and especially on small scale test on 10 students of biology education program IKIP Budi Utomo Malang. The result of student response analysis stated that the developed media is included in good enough category (88,57%). For media benefit criteria included in highly valid category (89.5%), media display criteria fall into very valid category (89.5%), and media material presentation criteria fall into very valid category (86.5%).